Prevalence of Sciatica in Female Tailors - Saliha Tanveer, Sadia Iftikhar, Farooq Islam, Asim Raza Thakur (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pain in low back region is the usual problem in general population, and especially common in those population where the majority of people sit. Prolonged sitting position or poor body ergonomics are the main source of developing low back pain and Sciatic nerve tightness, which can progress to sciatica. Adolescents and younger people are more likely to adopt poor posture and body ergonomics, which leads to sciatic nerve tightness. The purpose of this study was to determine the prevalence of sciatica among female tailors. Objective: To evaluate Sciatica in female tailors in Jhelum, Punjab Pakistan. Methodology: With a sample size of 318, a cross-sectional study was conducted on female tailors of District Jhelum. This study was done from March-June 2022 to September 2022 by using a non-probability convenient sampling technique, by selecting a female tailors of Jhelum, Punjab, who were between 18-60 years age, having work experience of at-least 1 year , who takes 1-2 times break , using a sitting /standing sewing machine for a long duration of time while a female tailors who having a history of lower limb surgery. Data were collected by using a self-created questionnaire with a reliability of 0.661, which was calculated after a pilot study considering inclusion and exclusion criteria. Patients were screened and asked for consult to participate in study. SLR test and VAS scale were used to assess the sciatica and pain in female tailors respectively. Results: About 318 participants took part in the study, with the primary findings indicating that Sciatic nerve tightness were found in 162(50.9percent) of tailors who had a positive diagnostic test (SLR test). Other respondents were found to have negative test results, indicating that they did not match the selection criteria. Practical Implication: It can be controlled by reducing risk factors of sciatica and to raise knowledge about low back pain and sciatica, so that people can avoid and protect them from low back pain and sciatica. Conclusion(s): It is concluded that female tailors are more prone to develop sciatica who are obese, work for long duration in sitting position. It can be controlled by reducing risk factors of sciatica and to raise knowledge about low back pain and sciatica, so that people can avoid and protect them from low back pain and sciatica. Keywords: Prevalence, Sciatica, SLR, Low Back Pain, Musculoskeletal Disease, VAS Scale.